2013
DOI: 10.1115/1.4025598
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Testing of Planar Stent Mesh Designs Using Carbon-Infiltrated Carbon Nanotubes

Abstract: This paper explores and demonstrates the potential of using pyrolytic carbon as a material for coronary stents. Stents are commonly fabricated from metal, which has worse biocompatibilty than many polymers and ceramics. Pyrolytic carbon, a ceramic, is currently used in medical implant devices due to its preferable biocompatibility properties. Micropatterned pyrolytic carbon implants can be created by growing carbon nanotubes (CNTs), and then filling the space between with amorphous carbon via chemical vapor de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…If the polyenes are the results of deformities or damage to the CNTs from oxidation as in the study by [17], then smaller polyenes would suggest less damage. The first explanation has some support from [5] who suggested that sp 2 sites in amorphous carbon prefer olefinic ordering. This is also supported by [10] who found that amorphous carbon is more likely to form polyene like structures as sp 2 sites increase.…”
Section: Peakmentioning
confidence: 97%
See 2 more Smart Citations
“…If the polyenes are the results of deformities or damage to the CNTs from oxidation as in the study by [17], then smaller polyenes would suggest less damage. The first explanation has some support from [5] who suggested that sp 2 sites in amorphous carbon prefer olefinic ordering. This is also supported by [10] who found that amorphous carbon is more likely to form polyene like structures as sp 2 sites increase.…”
Section: Peakmentioning
confidence: 97%
“…The process to grow the CI-CNTs is based upon the process used by Jones et al [5]. The summary of the procedure is summarized in seven steps as follows and portrayed in figure 1.…”
Section: Production Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…CICNT in quartz tubes were manufactured using a process that has been reported previously for at, silicon substrates. 27,28 The tubes were cut roughly 2 inches long and then in half lengthwise (Fig. 2a) to expose the inside curvature to thin lm deposition processes.…”
Section: Sample Fabricationmentioning
confidence: 99%